2013
DOI: 10.1590/s0080-623420130000400021
|View full text |Cite
|
Sign up to set email alerts
|

Insuficiência cardíaca: expressões do conhecimento das pessoas sobre a doença

Abstract: RESUMO ABSTRACTThis qualitative study characterized individuals with heart failure (HF) according to their sociodemographic, health, and treatment profiles and analyzed their knowledge on the disease and its treatment. A total of 42 volunteers with HF were interviewed at a cardiology hospital in São Paulo using a semi-structured questionnaire; the data were subjected to content analysis. The sample comprised mostly males and individuals older than 45 years old; the sample was classified as functional class II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 10 publications
(11 reference statements)
0
4
0
12
Order By: Relevance
“…Essa doença é responsável por altos custos hospitalares, por grande parte dos atendimentos de emergência, provoca perda da qualidade de vida e, muitas vezes, aposentadorias precoces com altos custos para o país (2) . O tratamento da IC é constituído pela associação da terapia farmacológica e não farmacológica.…”
Section: Introductionunclassified
“…Essa doença é responsável por altos custos hospitalares, por grande parte dos atendimentos de emergência, provoca perda da qualidade de vida e, muitas vezes, aposentadorias precoces com altos custos para o país (2) . O tratamento da IC é constituído pela associação da terapia farmacológica e não farmacológica.…”
Section: Introductionunclassified
“…Welfare is altered, generating incapacities, restrictions on routine habits, limitation of autonomy and independence, especially in the elderly. [16,17,19] A study carried out with elderly patients with HF demonstrated the perception they have regarding the nursing professionals who carry out activities in health education. These patients have reported perceptions related to the affective level, such as attention and affection, empathy in the nursing field is something essential, taking into account that individuals are dealt with in moments of fragility not only biological, but also psychic.…”
Section: Results and Discusionmentioning
confidence: 99%
“…[12] In all of the studies analyzed, it was observed that nursing education interventions aim not only to improve knowledge about HF but also, the behaviors that influence the illness. [15][16][17][18][19][20][21] Patients are given nursing care related to medication, food, rest, physical activity, as well as special care referring to the particular conditions of each patient. [20,21] …”
Section: Results and Discusionmentioning
confidence: 99%
“…Concordante com esses achados, pesquisa nacional que analisou o conhecimento de pessoas com IC sobre a doença identificou que este é fundamentado em experiências individuais, sem embasamento científico, mas por meio da percepção comum apreendida no manejo diário da IC 12 . Com isso, torna-se primordial que estratégias educativas delineadas pela equipe multidisciplinar sejam testadas e implementadas na assistência oferecida a essa população, a fim de clarificar o processo saúde/doença, favorecendo uma visão ampliada da gestão de autocuidado e qualidade de vida.…”
Section: Discussionunclassified